2021
DOI: 10.1186/s13287-021-02630-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of adult mammalian retinal stem cells in vivo via antagonism of BMP and sFRP2

Abstract: Background The adult mammalian retina does not have the capacity to regenerate cells lost due to damage or disease. Therefore, retinal injuries and blinding diseases result in irreversible vision loss. However, retinal stem cells (RSCs), which participate in retinogenesis during development, persist in a quiescent state in the ciliary epithelium (CE) of the adult mammalian eye. Moreover, RSCs retain the ability to generate all retinal cell types when cultured in vitro, including photoreceptors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…This notion is supported by (i) the increase in thickness of the ONL following treatment with CompA, (ii) the fact that treatment commenced following the completion of primary MNU-induced photoreceptor death, (iii) histological data suggestive of increased progenitor levels in the ONL following treatment, (iv) the presence of postnatal Msx1 lineage-derived cells in treated ONL, and (v) the magnitude and temporal profile of the sustained visual/retinal functional improvements. On the other hand, the continued existence of in vivo RSPCs in the adult mammalian eye remains controversial [8][9][10], and in our experiments, the numbers of detectable EdU and tdTomato-positive cells observed in the ONL are not sufficient to explain the observed functional regeneration, although this may correspond to our inability to properly detect all EdU (incomplete labeling, signal dilution, lack of EdU for the entire length of the experiment) and all tdTomato signals [11]. Therefore, another possibility is that functional regeneration may correspond to the recovery of pre-existing photoreceptors that did not die from the initial MNU insult.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…This notion is supported by (i) the increase in thickness of the ONL following treatment with CompA, (ii) the fact that treatment commenced following the completion of primary MNU-induced photoreceptor death, (iii) histological data suggestive of increased progenitor levels in the ONL following treatment, (iv) the presence of postnatal Msx1 lineage-derived cells in treated ONL, and (v) the magnitude and temporal profile of the sustained visual/retinal functional improvements. On the other hand, the continued existence of in vivo RSPCs in the adult mammalian eye remains controversial [8][9][10], and in our experiments, the numbers of detectable EdU and tdTomato-positive cells observed in the ONL are not sufficient to explain the observed functional regeneration, although this may correspond to our inability to properly detect all EdU (incomplete labeling, signal dilution, lack of EdU for the entire length of the experiment) and all tdTomato signals [11]. Therefore, another possibility is that functional regeneration may correspond to the recovery of pre-existing photoreceptors that did not die from the initial MNU insult.…”
Section: Discussionmentioning
confidence: 55%
“…While these postnatal cells are not thought to participate in retinogenesis [32], they do represent part of the ciliary body-derived population of cells capable of forming secondary neurospheres in vitro [11]. Using an inducible fluorescent Msx1CreERT2;tdTomato mouse line, tamoxifen induction was performed on postnatal days (P)11-P14 to label cells expressing Msx1 at these time points with tdTomato, allowing for the in vivo quantification of labelled postnatal Msx1-lineage cells during adulthood.…”
Section: Compounda Promotes In Vitro and In Vivo Rspc Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…Generating commercial-scale donor cell sources remains the key challenge for successful clinical translation. These technical hurdles have driven scientists and clinicians to seek in situ regenerative approach via small molecule or genetic stimulation to the Muller glial at the ciliary margin zone or peripheral retina [37]. In 2009, Dr. Qiu first demonstrated that adult human Understanding the Biology in Current Cell and Gene Therapy for Treating Macular Diseases DOI: http://dx.doi.org/10.5772/intechopen.1003722 retinal cells can be reprogrammed, forming retinal neurospheres and expressing photoreceptor progenitor surface markers (recoverin + nestin co expression), which for the first time challenged the century-old dogma of adult human retinal plasticity (G Qiu, UK Patent Application No.…”
Section: Photoreceptor Transplantation and Cell Reprogrammingmentioning
confidence: 99%